Recent Publications (Quarterly Journal of Economics, 1948)
Recent Publications Get access The Quarterly Journal of Economics, Volume 62, Issue 5, November 1948, Pages 794–797, https://doi.org/10.1093/qje/62.5.794 Published: 01 November 1948